Case report and review: Angiosarcoma with thrombocytopenia after total hip arthroplasty - Skants, Noora; Rönty, Mikko; Komulainen, Olli; Keski-Keturi, Miikka; Huotari, Kaisa; Alander-Pekkarinen, Maria; Sihvo, Marjut; Laitinen, Minna; Linko, Rita (Frontiers in Surgery, 2023)
Total hip arthroplasty (THA) is a common treatment for osteoarthritis, and it is also used for other indications, such as secondary arthritis due to developmental dysplasia of the hip. Various THA types may be complicated by osteolysis and an inflammatory pseudotumor due to an adverse reaction to metal debris. Rarely, THA has been associated with malignant tumors, but their causality remains unclear.In this case report, we describe a female patient with developmental dysplasia of the hip. She had undergone left metal-on-polyethylene THA, acetabular revision of the THA, and left total knee arthroplasty. Additionally, she had a history of dyslipidemia and telangiectasia of the eyes, anemia, hiatal hernia, and pleuritis. During a previous hospital admission due to pleuritis, a THA-associated mass (suspected to be a pseudotumor) had been detected. She was hospitalized due to swelling in her lower left limb, fatigue, and bruises. A clinical examination revealed anemia, thrombocytopenia, and growth of the suspected pseudotumor. Within six weeks, she presented with bleeding of the oral mucosa, hemoptysis, melena, severe thrombocytopenia that did not respond to treatment, elevated D-dimer and C-reactive protein levels, severe pain, increased osteolysis, and fractures around the THA. Infection or malignancy was suspected, but two trocar biopsies suggested an inflammatory pseudotumor. Since her anemia and thrombocytopenia were considered to have been caused by an inflammatory process within the suspected pseudotumor, her suspected pseudotumor and all THA components were surgically removed. However, she developed severe alveolar hemorrhaging and hypoxia, and she died two weeks after her surgery. Histopathological analysis of her surgical and autopsy samples revealed highly malignant angiosarcoma.Although individual cases of malignancies associated with THA have been reported, the literature lacks a clear association between THA and increased cancer risk. Most pseudotumors are nonmalignant. The patient's case presented in this report exemplifies the challenges to the differential diagnosis of a THA-associated pseudotumor and rare angiosarcoma. Atypically rapid tumor growth, severe osteolysis, and a deterioration in general well-being suggest malignant disease.